Introduction: The Challenges of Globalization for Workers: Transnational and Transborder Issues - Aguirre, Adalberto (Social justice, 2004)
Part of a special issue on social justice for workers in the global economy. The role of globalization, the closer integration of the world economy, in promoting an agenda that increases profits by depreciating labor and subjugates the interests of developing countries to those of the most powerful economic actors and nations is explored. The challenges that global capitalism and neoliberalism pose for workers in particular industries and countries are outlined, and the prospects for workers seeking greater justice are considered. A brief introduction to the special issue articles is provided.